Change in microplastic concentration during various temporal events downstream of a combined sewage overflow and in an urban stormwater creek - Forrest, Shaun A.; McMahon, Darryl; Adams, William A.; Vermaire, Jesse C. (Frontiers in Water, 2022)
Changes in microplastic concentrations were examined during various temporal events including heavy rain and snowmelt in a river and an urban stream receiving stormwater. Additionally, microplastic concentrations were measured in an urban river during an active combined sewage overflow event. Microplastic concentrations downstream of a combined sewage outfall were observed to increase seven times compared to ambient conditions. During heavy rainfall an increase of 50 times the microplastic concentration was observed in the urban creek with microplastic concentrations doubling in the urban river. However, the largest increase in microplastic concentration at both locations was observed during the primary snowmelt of spring, with microplastic concentrations increasing 114 times in the urban creek and 11 times in the urban river. These results suggest that more research is required to further establish the influence of both combined sewage overflows and snowmelt as a major temporal conduit of microplastics to freshwater environments.